Fractal Compression of Colored Animated Pictures - Basil Younis (Al-Rafidain Journal of Computer Sciences and Mathematics, 2012)
This research deals with the question of pressing two series of video images by using the pressing Fractal through the use of iterative function systems, where the film frame video acquired is divided after  each converting it to one type of the storage formulas for the image files independently. Then, the image is divided into non-overlapping range blocks with the size P×P, the biggest block of which is the overlapping domain one with the size 2P×2P. After that matching is made between rang blocks and each block of domain blocks to obtain domain blocks identical to range blocks. The purpose of making matching is to obtain the best domain block identical to rang block by using familiar transfers, to reduce the  volume of storage with the possibility of decompression and making a comparison between the time of compression and decompression. The research sample includes two series of video films from the city of Mosul, namely, the Nineveh bridge and the building of college of Computer Science and Mathematics at the University of Mosul, It is found that algorithm used is efficient as far as compression and decompression of color and moving images are concerned.